OPTIMALISASI PENCEGAHAN KORUPSI DALAM PENGELOLAAN DANA PENANGGULANGAN COVID-19 DI INDONESIA - Rizki Zakariya (Fakultas Hukum Universitas Malikussaleh, 2023)
The existence of Covid-19 has a socio-economic impact on Indonesian society. Therefore, the Government implemented policies to address the impact of Covid-19 on society. However, these efforts have weaknesses, namely the potential for corrupt practices, especially in the procurement of goods / services for the benefit of Covid-19 and the distribution of Cash Social Assistance in the community. This research is a juridical-normative legal research using a case approach and comparative approach. Then it is processed and analyzed qualitatively. The results of this study indicate that there are potential gaps in corrupt practices in the procurement of goods / services for overcoming Covid-19 and the distribution of Cash Social Assistance to the public. It started from the occurrence of conflicts of interest, bribes, price mark ups, deductions from recipients of Cash Social Assistance funds, and kickbacks. So the recommendation given is the need for LKPP collaboration with law enforcement institutions; optimization of the use of e-catalog, e-purchasing; strengthening the compliance of Ministries / Institutions / Regional Apparatus on LKPP recommendations; and the use of the article on money laundering for corporations, and the socialization of the prohibition on cutting Covid-19 funds by the village apparatus.